Towards Infrared Electronic Eyes: Flexible Colloidal Quantum Dot Photovoltaic Detectors Enhanced by Resonant Cavity. Issue 12 (15th February 2019) - Tang, Xin; Ackerman, Matthew M.; Shen, Guohua; Guyot‐Sionnest, Philippe
Abstract: Electronic eye cameras are receiving increasing interest due to their unique advantages such as wide field of view, low aberrations, and simple imaging optics compared to conventional planar focal plane arrays. However, the spectral sensing ranges of most electronic eyes are confined to the visible, which is limited by the energy gaps of the sensing materials and by fabrication obstacles. Here, a potential route leading to infrared electronic eyes is demonstrated by exploring flexible colloidal quantum dot (CQD) photovoltaic detectors. Benefitting from their tunable optical response and the ease of fabrication as solution processable materials, mercury telluride (HgTe) CQD detectors with mechanical flexibility, wide spectral sensing range, fast response, and high detectivity are demonstrated. A strategy is provided to further enhance the light absorption in flexible detectors by integrating a Fabry–Perot resonant cavity. Integrated short‐wave IR detectors on flexible substrates have peak D * of 7.5 × 10 10 Jones at 2.2 µm at room temperature and promise the development of infrared electronic eyes with high‐resolution imaging capability. Finally, infrared images are captured with the flexible CQD detectors at varying bending conditions, showing a practical approach to sensitive infrared electronic eyes beyond the visible range. Abstract : A potential route leading to infrared electronic eyes is demonstrated by exploring flexible colloidal quantum dot (CQD) photovoltaic detectors with mechanical flexibility, wide spectral sensing range, fast response, and high detectivity. Infrared images are captured with the flexible CQDs detectors at varying bending conditions, showing a practical approach to sensitive infrared electronic eyes beyond visible.